Internal validation of GlobalFilerTM kit using reduced reaction volume. Issue 1 (December 2019) - Almohammed, E.; Hadi, S.
Abstract: For approximately two decades, Microsatellites or Short Tandem Repeat (STR) markers have been the backbone for human identification testing in the forensic field. The expansion of STR multiplex kits can improve global sharing of STR profiles, rapid DNA typing, and DNA typing Flores et al. (2014). GlobalFiler™ kit is highly sensitive and has extremely high power of discrimination. An internal validation of GlobalFiler™ Kit was carried out to test the robustness of this kit through a range of internal validation studies including half volume reaction, reproducibility, sensitivity, specificity, stability, mixture, analytical threshold, sensitivity & stochastic threshold, heterozygous balance & stutter threshold studies in accordance with SGWDAM guidelines Scientific Working Group on DNA . Reference and real casework samples previously tested using other autosomal STR kits from forensic cases were used during the validation. It was demonstrated that the GlobalFiler™ kit has enhanced discrimination power, is robust and extremely useful for forensic casework.